Desempenho do "sensor capacitivo em meios porosos" em diferentes condições de salinidade - Santos, Clarissa Pereira dos (2017)
The capacitive methods of determination of soil moisture present great practicality and applicability in the agricultural environment vary depending on soil type, temperature and salinity. In this work, the objective was to verify the performance of the Moisture Capacitive Sensor in Porous Media submitted to saline media. The evaluated sensor provides electrical frequency values related to soil moisture and was developed at the Federal University of Ceará. It was evaluated the data supply when submitted to different electrical conductivities of the medium, referring to the salt solutions in different concentrations of potassium chloride (KCl), maintaining the constant temperature. The measurements were performed in an electric frequency range from kHz to MHz. Subsequently, the sensor performance was evaluated in the soil of sandy texture in different humidity and salinity. Correlating the measurements in relation to humidity, it was possible to identify the influence of the salts in the response given by the sensor when the distilled water was applied in relation to the use of KCl solutions in different concentrations. The influence of the salts was also considered in the variation of the measurement frequency to identify if the increase or decrease of the output frequency gave an alternative of adjustment of the system as to the influence of the salts. It was observed that the electrodes of the capacitive sensor of porous media show sensitivity to salinity when inserted in aqueous solutions with salinity up to 4 dS.m-1 of electrical conductivity. It was also identified that there was no significant difference in the attenuation of the salinity effect in the measurements made by the sensor in solution or in soil when using different resistors in the mounted RC circuit.